2018
DOI: 10.1155/2018/4756147
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ablation for Hepatocellular Carcinoma: Comparison of Various Ablation Techniques and Surgery

Abstract: Image-guided percutaneous ablation is considered best in the treatment of early-stage hepatocellular carcinoma (HCC). Ablation is potentially curative, minimally invasive, and easily repeatable for recurrence. Ethanol injection used to be the standard in ablation. However, radiofrequency ablation has recently been the most prevailing ablation method for HCC. Many investigators have reported that radiofrequency ablation is superior to ethanol injection, from the viewpoints of treatment response, local tumor cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 86 publications
2
73
0
6
Order By: Relevance
“…smaller sizes. MWA and RFA have high local tumor control abilities and result in low levels of invasion and are therefore recommended as the most appropriate treatment options of early-HCC (13,14). Previous studies had reported that first-generation MWA is a useful treatment for small HCC tumors (15,16), and in several reports, MWA and RFA have been reported to yield equivalent results in terms of therapeutic effects and complications (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…smaller sizes. MWA and RFA have high local tumor control abilities and result in low levels of invasion and are therefore recommended as the most appropriate treatment options of early-HCC (13,14). Previous studies had reported that first-generation MWA is a useful treatment for small HCC tumors (15,16), and in several reports, MWA and RFA have been reported to yield equivalent results in terms of therapeutic effects and complications (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…RFA is considered the standard of care for treatment of HCC of 3 cm or smaller [30]. Compared with RFA, MWA is associated with increased ablation temperatures, increased ablation zones, and a reduction in the heat-sink effect for HCC [31,32]. Besides, MWA is reported to induce lower risk of unintended injury for lesions abutting visceral organs [33].…”
Section: Discussionmentioning
confidence: 99%
“…The major risk factors of PLCs include chronic infection of hepatitis B/C viruses, excess alcohol consumption, non-alcoholic fatty liver disease, and a atoxin exposure [3,4]. Although current treatments, including percutaneous local ablation, surgical resection, and liver transplantation, improve the survival of patients with PLCs, PLC-correlated mortality still increases owing to population growth and high recurrence [1,5,6]. Therefore, to develop novel therapies for PLCs based on molecular studies is urgently needed.…”
Section: Introductionmentioning
confidence: 99%